Determinants of boat velocity during a 200 m race in elite paralympic sprint kayakers - Redwood-Brown, A. J.; Brown, H. L.; Oakley, B.; Felton, P. J. (International Journal of Performance Analysis in Sport, 2021)
This study investigates the relationships between boat velocity, stroke rate and displacement per stroke in Paracanoe 200m Sprint Kayak races. Data were analysed from 646, 200m efforts performed by 13 international Paracanoe athletes between 2017 and 2020 (Male: N= 6, female: N= 7) using boat-based GPS unit (Catapult S5). Significant differences between the Paralympic classifications were observed for boat velocity, stroke rate and displacement per stroke across both genders (p < 0.001) and Paracanoe classification (p < 0.001). Stroke rate was found to be the best predictor of boat velocity across classifications explaining between 13% and 34% of the variation. However, displacement per stroke was found to be more important for males than females potentially due to strength and anthropometric differences. Boat velocity, stroke rate and displacement per stroke values for the final 150m (measured in 50 m splits) indicated evidence for a mix of all-out and positive pacing strategies. The results of this study suggest intricate differences exist in Paracanoe Sprint Kayak based on gender and classification between athletes. This information is useful in the coaching of Paracanoe Sprint Kayak with evidence that physical preparation, training, and race strategy can be individualised to each athlete.